Experimental study of kerf width and taper on laser beam cutting acrylic sheet - Mohamad Yazid, Idris (2009)
This thesis is mainly about the study and analysis of the kerf width and taper on acrylic sheet based on the experiments conducted using laser beam cuffing machine and using various process parameter including laser power, cutting speed, cutting angle, nozzle gap and air pressure. The objective of this thesis is to study the kerf width and taper on laser beam cuffing process on acrylic sheet, to analyze the effect of various process parameters on kerf width and taper on laser beam cutting process and also to study about laser beam machining process. The thesis discuss the experimental analysis to predict the effect of the process parameter on kerf width and taper on acrylic sheet. The work piece that we are going to use in the experiment is acrylic sheet that is also known by trade names such as Plexiglas, Acrylite, and Lucite which is commonly used in industry. This material is great for glazing, windows, cutting boards, or anywhere a clear material is needed. Besides that, it is also has better optical clarity than glass, light weight, good impact strength and clear. As mentioned, the experiments is conduct using laser beam cutting machine. The specimen is cut in square shape then a slit is made through the center of specimen to determine the kerf width and taper. From the results, it is observed that the parameter set in the experiment on laser beam cutting had effect on kerf width and taper. Secondly, the cuffing speed, nozzle gap and laser power gives major impact on kerf width and taper. The kerf width and taper will increase considerably with the increase of laser power and nozzle gap and decreasing the cutting speed. The cutting angle and air pressure also gives some effect on kerf width and taper. Increasing cutting angle and air pressure will slightly increase the kerf width and taper. Low value of laser power, nozzle gap, cutting angle, air pressure and higher cutting speed will produce lowest /narrow kerf width and taper which means the finest cutting quality with good width and cut edge is produced.